Metabolômica de macrofungos cultivados em torta do caroço de algodão por espectrometria de massas - Souza, Miria de Almeida (2020)
The large production of agro-industrial waste arouses the search for sustainable alternatives. These residues are a great source of energy and biomass, and can be used for energy generation, biofuels and chemicals. Cotton is a crop that has great commercial importance. In addition to the production of fibers used in the manufacture of textiles, the seed is used to produce oil (liquid fraction) and cake/bran (solid fraction). Cotton seed cake/bran (TCA) has a significant amount of protein and carbohydrates, which can be used for animal nutrition. However, TCA has some antinutritional or toxic compounds for animal nutrition, such as gossypol. The use of microorganisms, among them, macrofungi has been a strategy to degrade/detoxify such chemical compounds and thus facilitate their use in mono or polygastric nutrition. However, it is necessary to identify the bioactive chemical compounds produced by the macrofungi, and in this case, the metabolomics based on mass spectrometry can be an applied tool to characterize the low molecular weight fungal metabolites. Thus, this work characterized the metabolites present in cottonseed cake after solid state fermentation of macrofungi, using untargeted metabolomics by Ultra-High Performance Liquid Chromatography - Mass Spectrometry (UHPLC-ESI-MS / MS). The resulting data were submitted to Principal Component Analysis (PCA) and compared to the database of Chemical Entities of Biological Interest and Kyoto Encyclopedia of Genes and Genomes. The PCAs of the macrofungi Schizophyllum commune (FPB 117) and Fistulina hepatica (CC102) showed significant changes in the profile of chemical compounds in cottonseed cake (in natura) after fungal fermentation. In the fermented (TCA + macrofungus) it was possible to identify chemical compounds of the classes of lipids, amino acids, oligosaccharides, nucleosides and nucleotides. The fermented with Pleurotus pulmonarius EF88 showed a chromatographic profile very close to the control, indicating the microbial cultivation process under the tested conditions did not show significant growth of the macrofungus. The untargeted metabolomics tool applied in this work proved to be efficient for the identification and characterization of metabolites from microbial fermentative processes in plant biomass. Such information contributes to studies involving the deconstruction of lignocellulosic biomass and the animal nutrition industry.